Intellectual disability nursing : an oral history project - Gates, Bob; Griffiths, Colin; Atherton, Helen L.; McAnelly, Su; Keenan, Paul; Fleming, Sandra; Doyle, Carmel; Cleary, Michelle; Sutton, Paul (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book presents oral histories of 31 long-serving intellectual disability nurses' careers and seeks to understand their experiences of and motives for working in this field. These recordings form a unique collection in the Royal College of Nursing's archives and will help put into perspective the current UK nursing workforce crisis.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: People with mental disabilities -- Medical care; Intellectual disability -- Nursing; Medical, Nursing -- General; Psychiatric nursing